2022
DOI: 10.3389/fendo.2022.923376
|View full text |Cite
|
Sign up to set email alerts
|

A Network Meta-Analysis of the Dose–Response Effects of Dapagliflozin on Efficacy and Safety in Adults With Type 1 Diabetes

Abstract: BackgroundMost patients with type 1 diabetes (T1DM) do not reach the blood glucose goal with treatment of insulin. In our research, we intended to estimate the therapeutic effect and safety of additional different doses of dapagliflozin on insulin treatment in T1DM.MethodsWe performed direct and indirect network meta-analysis using Bayesian models and graded different dosages of dapagliflozin by mixed therapy contrasts. We retrieved information from the PubMed, Embase, The Cochrane Library, Web of Science, Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“… Wang et al (2022 ) explored the quantitative relationship between dapagliflozin and loss of weight in T1DM patients and found that to achieve the plateau period in the loss of weight, 5 mg/day dapagliflozin was required for at least 41.6 weeks. Li et al (2022 ) found that dapagliflozin treatment significantly decreased HbA1c, insulin dosage, and body weight without increasing the risk of hypoglycemia in T1DM. However, the actual drug efficacy of dapagliflozin on HbA1c and whether there is a rebound from dapagliflozin efficacy on HbA1c remained unknown and thus cannot effectively guide an appropriate use of clinical medication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Wang et al (2022 ) explored the quantitative relationship between dapagliflozin and loss of weight in T1DM patients and found that to achieve the plateau period in the loss of weight, 5 mg/day dapagliflozin was required for at least 41.6 weeks. Li et al (2022 ) found that dapagliflozin treatment significantly decreased HbA1c, insulin dosage, and body weight without increasing the risk of hypoglycemia in T1DM. However, the actual drug efficacy of dapagliflozin on HbA1c and whether there is a rebound from dapagliflozin efficacy on HbA1c remained unknown and thus cannot effectively guide an appropriate use of clinical medication.…”
Section: Discussionmentioning
confidence: 99%
“…Dapagliflozin, a sodium–glucose cotransporter-2 inhibitor, has been approved for the treatment of type 2 DM (T2DM) ( Curovic et al, 2022 ; Lazzaroni et al, 2022 ). The mechanism of dapagliflozin is to promote glycemic disposal in an insulin-independent way, thereby decreasing postprandial glycemia and glycemic excursions accompanied by an inferior insulin demand without increasing the risk of hypoglycemia ( Li et al, 2022 ). It is interesting to note that research results suggest that dapagliflozin is a promising adjunct treatment to insulin which improves glycemic control in patients with inadequately controlled T1DM ( Dandona et al, 2017 ; Mathieu et al, 2018 ; Parkinson et al, 2019 ; Araki et al, 2020 ; Araki et al, 2021 ; Biester et al, 2021 ); meanwhile, it significantly decreases the glycated hemoglobin (HbA1c) ( Li et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dapagliflozin, the first-in-class SGLT2 inhibitor, was the subject of several trials, however, no conclusive advice on the optimal dose can be drawn [ 84 ]. A network meta-analysis of 13 RCTs ( n = 10,701) highlighted that treatment with dapagliflozin 5 mg and 10 mg decreased body weight from the baseline at MD: −3.2% (95%CI: −3.5 to −2.9%) and MD: −4.2% (95%CI: −4.6 to −3.9%) [ 84 ]. Maximum HbA1c efficacy of dapagliflozin was estimated to be −6.2% at week 9, irrespective of dapagliflozin doses.…”
Section: Treatments For Obesity In Patients With Type 1 Diabetesmentioning
confidence: 99%